Porównanie portfeli Markowitza z portfelami MVS na przykładzie portfela funduszu akcji ING w świetle behawioralnej struktury portfeli - Majewski, Sebastian (The comparison of Markowitz's portfolios with MVS portfolio on the example of ING investment fund portfolio in the case of behavioral structure of portfolios, 2006)
The main goal of this article is to compare two kinds of method of portfolio building in the case of risk pyramid. First this research was a trial of building effective portfolios for assets of ING Investment Fund portfolio with using Markowitz and MVS methods. Next author built portfolios with behavioral assumptions. The last part of the research was verifying how effective were portfolios (ex post) after half a year and after a year.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 321-329